Conceptualisation of an Animation-Based Educational Video on Zakat as an Educational Medium in Islamic Education - Ida Lusiana; Nurmawati (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This research aims to conceptualize an animation-based zakat learning video as an educational medium in Islamic Religious Education, focusing on needs analysis, instructional design, and the validity and reliability of measurement instruments. The study is motivated by the phenomenon of low understanding of zakat concepts among elementary and secondary school students, due to conventional teaching methods that are less effective for abstract material. This qualitative research employs a conceptual study approach through three stages: literature identification, analysis and synthesis, and concept formulation. The findings reveal: (1) needs analysis identified the necessity for visualizing abstract zakat concepts, alignment with the characteristics of the digital generation, practicality for teachers, simulation of calculation and distribution processes, and enhancement of student motivation; (2) video design was conceptualized through the integration of Cognitive Theory of Multimedia Learning, constructivism, and the ADDIE model; (3) evaluation instruments were developed through content validity (Aiken's V/CVI) and reliability (Cronbach's Alpha ≥ 0.70) involving four groups of assessors. These three conceptual pillars form a comprehensive framework for developing animation-based zakat learning videos that are effective and scientifically accountable.